Reproductive technology: ethical dilemma of Muslim legalistic opinions - Haneef, Sayed Sikandar Shah (Malayan Law Journal Sdn Bhd, 2014)
Reproductive medical technology has revolutionised the natural order of human procreation. Accordingly, some have celebrated its advent as a new and liberating determinant of kinship at the global level and advocate it as a right to reproductive healthwhileothershavefrowneduponitasavehiclefor‘guiltlessexchangeofsexual ﬂuid’andcommodiﬁcationofhumangametes.JuristicresponsesintheIslamicfaith rangefromunthinkingadoptiontorestrictiveuse.Whileutilisingthistechnologyto enablemarriedcouplestohavechildrenthroughtheuseoftheirownsexualmaterial is welcome, the use of third party, surrogacy and reproductive cloning are not in keeping with the sacrosanct principles of kinship, procreation through licit sexual intercourseandsocialcohesivenessforbuildingacohesivefamilyasupheldbyIslam. To examine such larger issues emanating from these new ways of human procreation,beyondthequestionoflegality,isapointwhichlegalscholarsinIslam, when issuing religious decrees, have not anticipated sufﬁciently. The article, henceforth, proposes to be an attempt to that end through a qualitative critical content analysis of selected literature written on the subject.